Patent Medicine Sellers: How Can They Help Control Childhood Malaria?. (3rd August 2010) - Akuse, Rosamund M.; Eseigbe, Edwin E.; Ahmed, Abubakar; Brieger, William R.
Abstract : Roll Back Malaria Initiative encourages participation of private health providers in malaria control because mothers seek care for sick children from them. This study investigated Patent Medicine Sellers (PMS) management of presumptive malaria in children in order to identify how they can assist malaria control. A cross-sectional survey of 491 PMS in Kaduna, Nigeria, was done using interviews and observation of shop activities. Most (80%) customers bought drugs without prescriptions. Only 29.5% were given instructions about doses. Between 40–100% doses of recommended antimalarials were incorrect. Some (22%) PMS did not ask questions about illness for which they were consulted. Most children treated in shops received injections. PMS facilitate homecare but have deficiencies in knowledge and practice. Interventions must focus on training them to accurately determine doses, give advice about drug administration, use oral medication, and ask about illness. Training should be made a prerequisite for registering and reregistering shops.